THE IMPORTANCE OF GRIT FROM AN EARLY AGE: BUILDING GRIT AND ADAPTIVE CHILDERN IN AN ERA OF CHANGING - Ajeng Dwi Juniar Pramono; Roswiyani Roswiyani; Monty P. Satiadarma (Media Inovasi Pendidikan dan Publikasi, 2025)
This psychoeducational community service activity aims to increase the understanding of PAUD X students' parents regarding grit that can build adaptive skills at an early age. All success indicators were achieved. During the material delivery session, the speaker explained through presentation materials that served as guidelines for the parents of students. Participant participation reached 80% (24 of the 30 parents invited and targeted), which means that although it did not reach 30 participants, it reached the minimum target of 80%. Based on the evaluation form, the parents also realized that this psychoeducational activity was beneficial for them and their children. Based on this explanation, it is evident that this community service activity has succeeded in achieving its targeted goals.